2021
DOI: 10.1111/acel.13448
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted macrophage metabolic reprogramming in aged soleus muscle during early recovery following disuse atrophy

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Peritoneal macrophages have previously been assessed for phagocytosis activity after polarisation with M1-like or M2-like stimuli with comparable phagocytic activity between young and old following M2 polarisation but a reduction in phagocytosis with age in M1-like macrophages, similar to our findings (39). Fix et al, also found an impairment in phagocytosis with age in pro-inflammatory BMDMs (16). In contrast to our findings in human MDMs, IFN/LPS stimulation has been found to increase phagocytosis in both young and old BMDMs compared with M 0 (17).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Peritoneal macrophages have previously been assessed for phagocytosis activity after polarisation with M1-like or M2-like stimuli with comparable phagocytic activity between young and old following M2 polarisation but a reduction in phagocytosis with age in M1-like macrophages, similar to our findings (39). Fix et al, also found an impairment in phagocytosis with age in pro-inflammatory BMDMs (16). In contrast to our findings in human MDMs, IFN/LPS stimulation has been found to increase phagocytosis in both young and old BMDMs compared with M 0 (17).…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, alveolar macrophages consistently show a reduction in phagocytic activity with age, including lower phagocytosis of apoptotic neutrophils (14) and E. coli (15). However, aged mouse bone marrow-derived macrophages (BMDM) showed no defect in uptake of zymosan particles (10), fluorescent particles (8), latex particles (16), or E. coli (17). In contrast, decreased phagocytosis with age was seen for uptake of apoptotic Jurkat cells (18), myelin fragments (9) and apoptotic N2A cell debris or E. coli bioparticles (19).…”
Section: Introductionmentioning
confidence: 99%
“…In coordination with macrophages, FAPs play an essential role in the proper remodeling of skeletal muscle following injury (Abramowitz et al, 2018) yet are functionally impaired with aging (Fix et al, 2021; Lukjanenko et al, 2019; Reidy et al, 2019; Schuler et al, 2021). While the necessity of FAPs for full resolution from muscle injury is well understood (Murphy et al, 2011), less is known about FAP senescence in muscle repair and remodeling after disuse, especially in aged adults.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the importance of macrophages in muscle remodeling is well understood as the absence of macrophages corresponds with muscle fibrosis and impaired muscle recovery (Arnold et al, 2007; Martinez et al, 2010; Ochoa et al, 2007) while in humans, muscle macrophage content positively correlates with muscle size after exercise training (Walton et al, 2019). Interventional therapy such as metformin is particularly relevant in this context since macrophage and FAP function are disrupted during recovery in aging (Fix et al, 2021; Lukjanenko et al, 2019; Reidy et al, 2019; Schuler et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…HIF-1α induces the binding of GLUT1, which controls glucose transport, and related genes during glycolysis by forming a dimer with HIF-1β and the intranuclear hypoxia response element on the target gene (54). In aging skeletal muscle, HIF-1α downregulation inhibits its downstream GLUT1, affecting macrophage glycolysis, thereby inhibiting its M1 polarization and phagocytosis (55). In addition, the drug silver forgesine degrades the proteasome of HIF-1α by affecting the expression of GLUT1, PKM, PDK1, lactate dehydrogenase (LDH)A and PFK, which further inhibits macrophage glycolysis, thereby limiting their polarization to the M1 type (56).…”
Section: Effect Of Metabolic Reprogramming Of Tams On Their Polarizat...mentioning
confidence: 99%